Spraying high concentrations of chelated zinc enhances zinc biofortification in wheat grain - Xu, Meng; Liu, Mengjiao; Si, Linlin; Ma, Qingxu; Sun, Tao; Wang, Jun; Chen, Kaijun; Wang, Xiangjie; Wu, Lianghuan (Society of Chemical Industry, 2022)
BACKGROUND Foliar application of highly concentrated ZnSO4 fertilizer improves Zn biofortification in wheat grains. However, excess ZnSO4·7H2O concentration (≥5 g kg−1, w v−1) has been associated with leaf burn and yield loss, necessitating Zn sources with a high threshold concentration. The aim of this study, based on a 2 year field experiment conducted on wheat cultivated in acidic and alkaline soil, was to identify a suitable Zn formulation with a high Zn concentration or efficient adjuvant to achieve optimal Zn biofortification levels without compromising agronomic performance.